A high-precision bidirectional time-transfer system over a single fiber based on wavelength-division multiplexing and time-division multiplexing - Guo, Xinxing; Liu, Bo; Kong, Weicheng; Quan, Honglei; Zhang, Yucan; Liu, Tao; Dong, Ruifang; Zhang, Shougang (Frontiers in Physics, 2023)
In this paper, a high-precision bidirectional time-transfer system over a single fiber based on wavelength-division multiplexing and time-division multiplexing (SFWDM-TDM) is proposed, which combines the advantages of wavelength-division multiplexing and time-division multiplexing. It uses two dense wavelength-division channels to effectively suppress the problem of optical fiber reflection. At the same time, the time-division multiplexing method is used in combination with sampling and holding the time to complete the multi-user task. In hardware, we optimized the carrier processing and the high-precision time-delay control module of the SFWDM-TDM system to complete high-precision time-transfer equipment. In software and algorithm, the optical fiber time-interval measurement method and measurement times are optimized, and the SFWDM-TDM system reaches a synchronization accuracy of 8.9 ps at 1 s. Finally, a real-time detection mechanism with self-recovery ability is added to the system. This lays the foundation for a reliable, long-distance, high-precision, and multi-user mode optical fiber time- and frequency-transfer network.